KRISIS IDENTITAS DAN KRISIS TERHADAP RELASI KUASA AGAMA DALAM NOVEL TUHAN IZINKAN AKU MENJADI PELACUR KARYA MUHIDIN M. DAHLAN - Ridwan Ridwan; Hamriani Hamriani (Universitas Galuh, 2026)
This study aims to examine the discourse of religious power operating in shaping and controlling individual identity, and the main character resists the hegemony using qualitative research methods. In the novel Tuhan Ijinkan Aku Menjadi Pelacur by Muhidin M. Dahlan, it presents a narrative that challenges the dominant religious discourse by telling the story of a woman's identity crisis who experiences existential turmoil due to the pressure of social and religious norms. The analysis step is to identify the main character's struggle against the dominance of religious discourse through the Critical Discourse approach. Meanwhile, from an existentialist perspective, this study examines the main character's search for the meaning of life amidst alienation, freedom of choice, and her efforts to reclaim authority over herself. The results of the analysis show that this novel reflects the tension between socio-religious determination and individual freedom, while also offering criticism of religious dogma that inhibits human subjectivity. Thus, this study contributes to the understanding of power relations in religious discourse and its implications for the construction of individual identity in society.